Analisis Framing Pemberitaan Kebakaran Hutan dan Lahan Di Provinsi Sumatera Selatan pada Media Detik.com Edisi Agustus-September 2020 - Wardana, Muhammad Wisnu; Herman, Achmad (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2024)
The incident of forest fires in South Sumatra Province became one of the news topics that were actually presented in various mass media, one of which was Detik.com. This study aims to determine the framing of forest and land fire reports published by Detik.com using the perspective of Murray Edelman's framing model. This research uses Murray Edelman's framing analysis model approach, namely categorization and ideology. This research is a qualitative descriptive type. The unit of analysis in this news is texts related to forest and land fires that occurred in South Sumatra which were published by Detik.com media from August 8, 2020, to September 1, 2020, based on observations found in 6 (six) reports of forest and land fires. The results showed that Detik.com framed the news of forest and land fires in South Sumatra by forming a new reality that the Governor of South Sumatra, Herman Deru, was a superior figure and a leader who resolved the problems of forest and land fires that occurred in the Musi Banyuasin area, Banyuasin. , Ogan Ilir, Ogan Komering Ilir and Panukal Abab Lematang Ilir. The efforts made by Herman Deru in resolving forest and land fires are by utilizing great facilities, both from professional personnel and up-to-date tools, and involving foreign assistance.